To suppress tin whisker growth by using (100)-oriented copper - Han-Wen Lin; Jia-Ling Lu; Chih-Chia Hu; K.N. Tu; Chih Chen (Journal of Materials Research and Technology)
Effect of Cu crystallographic orientations on the Sn whisker growth is investigated in this study. Three types of Cu under-layer (randomly, <111>, <100>-oriented) were prepared for electroplating of pure Sn. After 672 h of room temperature (RT) storage, a lot of whiskers were found on the Sn surface electroplated on the randomly-oriented Cu, whereas very few whiskers can be seen on those electroplated on the <111>− or the <100>-oriented Cu. It is also found that the behavior of intermetallic compound (IMC) growth at the Sn–Cu interface is quite different between the randomly- and specifically-oriented Cu films, which leads to divergent phenomena of Sn whisker growth. Furthermore, after 7944 h of RT storage, both the <111>− and the <100>-oriented Cu films are proven to be effective on preventing Sn whisker growth. Orientation analysis indicated the Sn grains on the <111>− and the <100>-oriented Cu possesses <110> preferred orientation, which may slow down the formation of the Cu–Sn IMCs.